Systematics of the blindsnakes (Serpentes: Scolecophidia: Typhlopoidea) based on molecular and morphological evidence - Pyron, Robert Alexander; Wallach, Van (Zootaxa, 2014)
The blindsnake superfamily Typhlopoidea (Gerrhopilidae, Typhlopidae, and Xenotyphlopidae) is a diverse, widespread part of the global snake fauna. A recent systematic revision based on molecular phylogenetic analyses and some morphological evidence presented a preliminary solution to the non-monophyly of many previously recognized genera, but additional clarification is needed regarding the recognition of some species and genera. We rectify these problems here with a new molecular phylogenetic analysis including 95 of the 275 currently recognized, extant typhlopoids, incorporating both nuclear and mitochondrial loci. We supplement this with data on the external, visceral, and hemipenial morphology of nearly all species to generate a revised classification for Typhlopoidea. Based on morphological data, we re-assign Cathetorhinus from Typhlopidae to Gerrhopilidae. Xenotyphlopidae maintains its current contents (Xenotyphlops). In Typhlopidae, one monotypic genus is synonymized with its larger sister-group as it cannot be unambiguously diagnosed morphologically (Sundatyphlops with Anilios), and two genera are synonymizedwith Typhlops (Antillotyphlops and Cubatyphlops), as they are not reciprocally monophyletic. The genus Asiatyphylops is renamed Argyrophis, the senior synonym for the group. We erect one new genus (Lemuriatyphlops) for a phylogenetically distinct species-group in Asiatyphlopinae. Fourteen of eighteen recognized typhlopid genera are maintained in four subfamilies: Afrotyphlopinae (Afrotyphlops, Grypotyphlops [re-assigned from Asiatyphlopinae], Letheobia, and Rhinotyphlops), Asiatyphlopinae (Acutotyphlops, Anilios, Cyclotyphlops, Indotyphlops, Malayotyphlops, Ramphotyphlops, and Xerotyphlops), Madatyphlopinae (Madatyphlops), and Typhlopinae (Amerotyphlops and Typhlops), some with altered contents. Diagnoses based on morphology are provided for all 19 typhlopoid genera, accounting for all 275 species. This taxonomy provides a robust platform for future revisions and description of new species.